Study Of Enterotoxigenicity Of B. Cereus Emetic Strain By Skin Vasopermeability Reaction In Rabbits And Poultry - MUSVI S ALTAF,; ASIF IQBAL,; MANZOOR AHMAD,; DR.SYED ARSHID HUSSAIN,; RAYAZ AHMAD,; WILLAYAT M.M, (International Journal of Pharma and Bio Sciences, 2012)
The present study pertains to the toxigenicity of Bacillus cereus emetic strain isolated from raw milk and milk products in Kashmir valley. The study was conducted during October 2009-June 2010. A total No. of 175 samples comprising of 50 raw milk and 125 of different milk products were tested. Bacillus cereus emetic strains were isolated from 8 of the raw milk and 20 of the milk product samples, (6, 5, 4, 3 and 2 samples out of 25 each of rasgulla, burfi, ice-cream, rasmalai and cheese/paneer, respectively). B. cereus emetic strains were isolated from 16 percent of the raw milk. Among the different milk products analysed B. cereus emetic strains could be isolated from 20, 24, 12, 16 and 8 percent of burfi, rasgulla, rasmalai, ice-cream and cheese/paneer, respectively. The field isolates and the standard strain of Bacillus cereus had similar cultural, morphological and biochemical characteristics. Raw milk, burfi and ice-cream revealed biotypes 2, 5 and 7, whereas, rasmalai and cheese/paneer revealed only biotype 5. Biotypes 2 and 5 were recovered from rasgulla. Bacillus cereus emetic enterotoxin (BCEET) produced by field isolates and the standard strain produced comparable vascular permeability reaction on intradermal inoculation. The development of moderate to severe VPR was observed in rabbit skin, where as there was mild VPR in poultry skin.